Condensation driven by a quantum phase transition (2022)
The grand canonical thermodynamics of a bosonic system is studied in order to identify the footprint of its own high-density quantum phase transition. The phases displayed by the system at zero temperature establish recognizable patterns at finite temperature that emerged in the proximity of the boundary of the equilibrium diagram. The gaped phase induces a state of collectivism/condensation at finite temperature in which population cumulates into the ground state in spite of inter- acting attractively. The work sets the foundation to approach the effect of attraction in the formation of a molecular condensate.